Manejos de cereais de inverno em sistema de integração lavoura pecuária e sua influencia sobre as propriedades físicas do solo, resíduos culturais e plantas daninhas - Piano, Jeferson Tiago (2014)
The study aimed and was conducted to evaluate the effects of different managements of cereals grown and subjected to grazing on soil physical properties, quantity and nutrient content of winter crop residues, besides the incidence of weeds. The study was conducted in the experimental area of the State University of West Paraná - Campus Marechal Cândido Rondon in Dystrophic Oxisol. The experimental design was randomized blocks in split-plot, with four replications. The treatments consisted of three different winter cereals (oats IPR 126, wheat and triticale BRS Tarumã IPR 111) in bands A and managements in B bands: ungrazed , one grazing and two grazing. With respect to soil physical properties (macroporosity, microporosity, total porosity and density), determined by collecting soil core, it was found that they suffered minor influences, with the exception of soil density due to treatments, evaluations after harvest of winter cereals and soybeans. The resistance to penetration, determined with an impact penetrometer, was influenced by the crop after harvest of winter cereals and by management after the soybean harvest in 20-25 cm layer and 25-30 cm depth. The different winter cereals used influenced the amount of remaining organic waste, the levels of C and P in the C:N. The largest amount of crop residues was found that the management was not performed grazing. Through the inventory square method, were identified 11 families and 16 species of weeds in the area, highlighting the Poaceae and Asteraceae families